A basic model for the propagation of ideologies - Mata Boschini, Luis Diego (2022)
Ideas and ideologies move the world and are involved in almost every aspect of human life and society. This paper presents a mathematical model for the propagation of two different ideologies in a group of people that could convert or not to one of the ideologies. This model allowed us to analyze which relations between parameters influence the survival and dominance of an ideology. The basic reproductive number was computed and numerical simulations were performed to analyze different scenarios.